Development and Evaluation of Magnetite Loaded Alginate Beads Based Nanocomposite for Enhanced Targeted Analgesic Drug Delivery - Das, Amrita (2025)
Iron oxide-based nanoparticles, such as magnetic nanoparticles (MNPs), have gained significant attention in the area of drug delivery due to their unique magnetic properties, allowing for precise targeting and controlled release of therapeutic agents. Several successful research studies were reported with combinations of magnetic nanoparticles and polysaccharides such as sodium alginate, chitosan, cellulose, etc. The presented research work is based on synthesising MNPs via the co-precipitation method and their successful encapsulation within alginate beads, serving as a promising drug delivery system for aceclofenac, a model drug. The physical and chemical characteristics of both the prepared magnetite nanoparticles and the aceclofenac-loaded MNPs alginate beads were thoroughly examined using scanning electron microscopy (SEM), high-resolution transmission electron microscopy (HRTEM), Fourier-transform infrared spectroscopy (FTIR), powder X-ray diffraction (PXRD), and vibrating sample magnetometry (VSM). Furthermore, a drug release study was conducted to evaluate the release kinetics of aceclofenac from the prepared MNP alginate beads. The magnetic characteristics of magnetite and MNP beads shed light on the potential application of novel drug delivery systems for magnetically targeted therapeutic interventions. The present research offers valuable insights into the development of magnetic nanoparticle-based drug carriers, paving the way for enhanced drug delivery strategies in the field of pharmaceutical sciences.